Retinal vascular injuries and intravitreal human embryonic stem cell-derived haemangioblasts - Wang, Jin-Da; Jonas, Jost B. (Acta ophthalmologica, 2017)
Objective: To investigate whether intravitreally applied haemangioblasts (HB) derived from human embryonic stem cells (hESCs) are helpful for the repair of vascular damage caused in animals by an oxygen-induced retinopathy (OIR), by an induced diabetic retinopathy (DR) or by an induced retinal ischaemia with subsequent reperfusion. Methods: Human embryonic stem cell-derived HBs were transplanted intravitreally into C57BL/6J mice (OIR model), into male Wistar rats with an induced DR and into male Wistar rats undergoing induced retinal ischaemia with subsequent reperfusion. Control groups of animals received an intravitreal injection of endothelial cells (ECs) or phosphate-buffered saline (PBS). We examined the vasculature integrity in the mice with OIR, the blood-retina barrier in the rats with induced DR, and retinal thickness and retinal ganglion cell density in retina flat mounts of the rats with the retinal ischaemic-reperfusion retinopathy. Results: In the OIR model, the study group versus control groups showed a significantly (p < 0.001) smaller retinal avascular area [5.1 ± 2.7%;n = 18 animals versus 12.2 ± 2.8% (PBS group; n = 10 animals) and versus 11.8 ± 3.7% (EC group; n = 8 animals)] and less retinal neovascularization [6.3 ± 2.5%;n = 18 versus 15.2 ± 6.3% (n = 10; PBS group) and versus 15.8 ± 3.3% (n = 8; EC group)]. On retinal flat mounts, hESC-HBs were integrated into damaged retinal vessels and stained positive for PECAM (CD31) as EC marker. In the DR model, the study group versus the EC control group showed a significantly (p = 0.001) better blood-retina barrier function as measured at 2 days after the intravitreal injections [study group: 20.2 ± 12.8 μl/(g × hr); n = 6; versus EC control group: 52.9 ± 9.9 μl/(g × hr; n = 6)]. In the retinal ischaemia-reperfusion model, the groups did not differ significantly in retinal thickness and retinal ganglion cell density at 2, 5 and 7 days after baseline. Conclusion: By integrating into damaged retinal vessels and differentiating into ECs, intravitreally administered hESC-HBs may have partially repaired a retinal vascular injury caused by OIR model and DR.
Gesehen am 08.10.2018